Role of the hippocampus and orbitofrontal cortex during the disambiguation of social cues in working memory - Ross, Robert S. (2013)
Human social interactions are complex behaviors requiring the concerted effort of multiple neural systems to track and monitor the individuals around us. Cognitively, adjusting our behavior based on changing social cues such as facial expressions relies on working memory and the ability to disambiguate, or separate, representations of overlapping stimuli resulting from viewing the same individual with different facial expressions. We conducted an fMRI experiment examining brain regions contributing to the encoding, maintenance and retrieval of overlapping identity information during working memory using a delayed match-to-sample (DMS) task. In the overlapping condition, two faces from the same individual with different facial expressions were presented at sample. In the non-overlapping condition, the two sample faces were from two different individuals with different expressions. fMRI activity was assessed by contrasting the overlapping and non-overlapping condition at sample, delay, and test. The lateral orbitofrontal cortex showed increased fMRI signal in the overlapping condition in all three phases of the DMS task and increased functional connectivity with the hippocampus when encoding overlapping stimuli. The hippocampus showed increased fMRI signal at test. These data suggest lateral orbitofrontal cortex helps encode and maintain representations of overlapping stimuli in working memory while the orbitofrontal cortex and hippocampus contribute to the successful retrieval of overlapping stimuli. We suggest the lateral orbitofrontal cortex and hippocampus play a role in encoding, maintaining, and retrieving social cues, especially when multiple interactions with an individual need to be disambiguated in a rapidly changing social context in order to make appropriate social responses.